Feel’d Notes in Public Places: Affective Artful Expression for Engagement and Transformation - Mason, Stephanie (Engaged Scholar Journal, 2022)
For my doctoral research into adults’ informal learning through material objects in four public places in Halifax, Nova Scotia, I used sketchbooks as fieldnote journals. In contrast to objective observations, I recorded during my site visits a panoply of overheard conversations, drawings, remarks, puns, encounters, temperatures, and colours. These and other elements comprised my experiences in each site, and I wanted to represent their gist and connotations through multiple forms of expression. This approach aligns with arts-informed research methodology that celebrates complexity and shared meaning-making with engaged scholarship. I used these notes to produce for each site a written vignette, to introduce and reacquaint others with that place; two of these vignettes appear in the following report. In translating what I came to call my “feel’d,” not “field,” notes into these written pieces, I gleaned new understandings about scribbling and scrawling expressive, affective feel’d notes. I found that engagement enriched my research process, and also fostered a greater awareness of place meanings. I recognize that transformed notetaking has a bearing on understanding, research process, people/communities, and places, and offers methodological insights that carry out and further engaged scholarship knowledge.